To love and be wise - Tey, Josephine, 1896 or 1897-1952 (Simon & Schuster, 2008)
"Literary sherry parties were not Alan Grant's cup of tea. But when the Scotland Yard Inspector arrived to pick up actress Marta Hallard for dinner, he was struck by the handsome young American photographer, Leslie Searle. Author Lavinia Fitch was sure her guest "must have been something very wicked in ancient Greece," and the art colony at Salcott St. Mary would have agreed." -- Back cover.